1968
DOI: 10.1139/v68-243
|View full text |Cite
|
Sign up to set email alerts
|

The photolysis of benzil in cyclohexane solution

Abstract: Benzil has been irradiated in cyclohexane solution. The principal products are: benzoic acid; benzal-dehyde; phenyl cyclohexyl ketone; benzoin; benzoin benzoate; a compound tentatively identified as desyl benzoyloxydesyl ether; another compound not yet identified; and approximately one-third of the reacted benzil that was not accounted for. A small amount of unsaturation is also found. As long as there is enough benzil present (presumably to absorb all of the light) the benzil disappearance is linear with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The main product observed upon UV light irradiation was compound (±)-S1. Bunbury reported that one of the major decomposition pathways of benzil in cyclohexane under UV light irradiation is the carbonyl-carbonyl homolysis to afford benzoyl radicals [25]; thus, we speculate that the stepwise, double addition of such intermediates onto the C=C double bond of 2a leads to the formation of (±)-S1. Importantly, we safely excluded that the latter compound is formed upon UV lightpromoted photolysis of the oxetane product (see Sect.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The main product observed upon UV light irradiation was compound (±)-S1. Bunbury reported that one of the major decomposition pathways of benzil in cyclohexane under UV light irradiation is the carbonyl-carbonyl homolysis to afford benzoyl radicals [25]; thus, we speculate that the stepwise, double addition of such intermediates onto the C=C double bond of 2a leads to the formation of (±)-S1. Importantly, we safely excluded that the latter compound is formed upon UV lightpromoted photolysis of the oxetane product (see Sect.…”
Section: Discussionmentioning
confidence: 81%
“…Quite interestingly, when the irradiation was carried out with shorter wavelengths (e.g. 390 nm) uncontrolled photodecomposition of benzil was observed [25]; on the other hand, light is essential for the reaction to occur and benzil 1a is photostable when irradiated in neat cyclohexane at 456 nm (see Scheme S2 in the SI). It is important to mention here that 2a does not absorb in the investigated window (> 310 nm) and it is not accountable for the observed photoreactivity [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photo-reaction of benzil in cyclohexane has already been reported (1). This study has been extended using 2-propanol and cumene as solvents.…”
Section: Introductionmentioning
confidence: 76%
“…produced either abstract hydrogen from the solvent or react with benzil as proposed by Bunbury and Wang (1). Then the proportion of benzaldehyde should increase with the ease of hydrogen abstraction from the solvent but no such correlation is found; cyclohexane 6.2%, cumene 7.4 %, 2-propano16 %.…”
Section: -1mentioning
confidence: 96%